Implikasi Takko Binoto dalam Adat Pernikahan Mandailing Terhadap Hak Perempuan dan Hukum Adat - Riza Anggraini; Tetti Eka Purnama; Susi Fitria Dewi; Zaky Farid Luthfi (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study aims to identify the impact (implications) of Takko Binoto in Mandailing marriage customs on women's rights and customary law. This study was conducted specifically in South Kauman, Pasaman Regency. The method used is descriptive qualitative, with data collection techniques through observation, interviews with 13 informants, and documentation. Data validity testing uses technical triangulation. Data analysis techniques are carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the stages of marriage implementation through Takko Binoto begin with the process of reporting the Takko Binoto perpetrator to Harajaon, the customary deliberation process (marpokat), the diplomatic process on the part of women, the determination of sinamot (dowry) and the day of inauguration and finally the maradat process. The influence of Takko Binoto on women's position and rights includes changes in social status and acceptance within the husband's family, high dependence on customary law and limited support networks, unclear inheritance and economic rights dependent on the kindness of the husband's family, and psychological pressure and the burden of proving oneself. This research emphasizes the importance of critically reevaluating this customary practice to protect legal certainty and women's fundamental rights in society. The critical revaluation referred to is not merely reassessing the procedures for implementing the tradition but rather fundamentally re examining how this practice has a direct impact on the certainly of customary law and the fulfilment of woman’s fundamental rights.